A note on Loewe-Marchand's Soul of Mhyrra (Madrid, Galería Nicolás Cortés) - Lorenzo Bartoli (Dante e l'Arte, 2023)
The painting by Frédéric Loewe-Marchand, The soul of Myrra (Madrid, Galería Nicolás Cortés), exhibited in Rome in 2021, in the context of the exhibition on Inferno, curated by Jean Clair for the Scuderie del Quirinale, is a wonderful example, vurtually unknown prior to the roman exhibition to the general public, of the interest of French Academic pianters towards Dante’s Comedy. The beutiful frontale nude depicted by Loewe Marchand, though, is also n explicit reaction to Dore’s Myrra, becoming, in this way, a painting which trscend the academic to involve the french art tradition of the XIX century, from Delacroix to Rodin.